Impact and Washback in Language Teaching: A Systematic Review of Theory, Evidence, and Emerging Trends - Sumarni; Muhammad Tahir; Muhammad Qurays; Aphariana Zaidah; Sari Agung Sucahyo (Universitas Islam Negeri Palopo, 2026)
This Background: Impact and washback—the influence of language tests on teaching, learning, curriculum, and society—are recognized as core qualities of language test usefulness (Phakiti, 2016; Bachman & Palmer, 1996). Despite three decades of scholarship since Alderson and Wall's (1993) foundational work, no PRISMA-compliant systematic review has synthesized the full scope of this literature incorporating post-2020 empirical developments and emerging digital assessment contexts. Objectives: To systematically map the theoretical landscape of impact and washback research, synthesize recent empirical evidence (2020–2025), and identify emerging frontiers including digital and AI-assisted assessment washback. Methods: A systematic narrative synthesis following PRISMA 2020 guidelines (Page et al., 2021). Databases searched: ERIC, Scopus, Google Scholar, Springer Nature Link, Wiley Online Library, and JSTOR. Eligibility criteria: peer-reviewed studies in English or Indonesian; focus on language test impact, washback, or related assessment consequences; publication 2000–2025 with particular emphasis on 2020–2025. Results: Of 247 records identified, 51 studies met inclusion criteria after full-text screening. Findings indicate a shift from linear test-cause models to stakeholder-ecological frameworks (Rahman et al., 2023), suggest that teacher beliefs and assessment literacy function as key mediating variables in washback, and document emerging washback phenomena in digital and AI-assisted assessment contexts (Jang & Sawaki, 2025). Notably, the corpus is geographically concentrated in Asian contexts, which should be considered when interpreting the generalizability of findings. Conclusions: Washback is a complex, multi-stakeholder phenomenon whose direction appears closely associated with teacher assessment literacy, institutional culture, and test construct breadth. Equity-centered assessment reform, responsible AI assessment design, and sustained teacher professional development are identified as high-leverage interventions for promoting positive washback, with particular relevance to the Indonesian EFL context.